2020
DOI: 10.1038/s41598-020-63515-5
|View full text |Cite
|
Sign up to set email alerts
|

Data-driven segmentation of audiometric phenotypes across a large clinical cohort

Abstract: Pure tone audiograms are used to assess the degree and underlying source of hearing loss. Audiograms are typically categorized into a few canonical types, each thought to reflect distinct pathologies of the ear. Here, we analyzed 116,400 patient records from our clinic collected over a 24-year period and found that standard categorization left 46% of patient records unclassified. To better account for the full spectrum of hearing loss profiles, we used a Gaussian Mixture Model (GMM) to segment audiograms witho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 36 publications
(44 reference statements)
2
17
0
Order By: Relevance
“…Various studies have used functional assessments to characterize ARHL and ARVL (Figure 3). These studies have shown that agerelated hearing loss assessed by pure-tone audiograms begins at 40 years of age and progresses bilaterally from high to low frequencies (summarized in Parthasarathy et al, 2020). The rate of hearing decline with age is highly variable (Gates and Cooper, 1991).…”
Section: Age-related Changes In the Anatomy And Function Of The Cochlea And Vestibular End Organsmentioning
confidence: 99%
“…Various studies have used functional assessments to characterize ARHL and ARVL (Figure 3). These studies have shown that agerelated hearing loss assessed by pure-tone audiograms begins at 40 years of age and progresses bilaterally from high to low frequencies (summarized in Parthasarathy et al, 2020). The rate of hearing decline with age is highly variable (Gates and Cooper, 1991).…”
Section: Age-related Changes In the Anatomy And Function Of The Cochlea And Vestibular End Organsmentioning
confidence: 99%
“…(2) The test would be applicable even to individuals with audiometric hearing loss. This is because most individuals with hearing loss have a sloping audiogram with highfrequency loss (Parthasarathy et al, 2020), and the BMLD effect is known to be largely preserved when the low-frequency loss is not substantial (Jerger et al, 1984). Participants had to correctly respond to five out of six trials in each task to pass the headphone screening and proceed to the other tasks in the study.…”
Section: Headphone-use Screeningmentioning
confidence: 99%
“…There have been some attempts to stratify HI listeners based on the shapes of their audiograms. Several classification schemes have been proposed in earlier studies, some of which were based on data-driven approaches (Bisgaard, Vlaming and Dahlquist 2010; Chang, Yoon, Kim, Baek, Cho, Hong, Kim and Moon 2019; Parthasarathy, Romero Pinto, Lewis, Goedicke and Polley 2020), where computational methods for data analysis were used for identifying the most common audiometric profiles. Based on results from human temporal bone studies, Schuknecht and Gacek (1993) proposed four different types of age-related hearing loss: sensory presbycusis, neural presbycusis, metabolic presbycusis and mechanical presbycusis.…”
Section: Introductionmentioning
confidence: 99%